Rapeseed oil-rich diet alters in vitro menadione and nimesulide hepatic mitochondrial toxicity - Monteiro, João P. (2013)
Diet-induced changes in the lipid composition of mitochondrial membranes have been shown to influence physiological processes. However, the modulation effect of diet on mitochondrially-active drugs has not yet received the deserved attention. Our hypothesis is that modulation of membrane dynamics by diet impacts drug-effects on liver mitochondrial functioning. In a previous work, we have shown that a diet rich in rapeseed oil altered mitochondrial membrane composition and bioenergetics in Wistar rats. In the present work, we investigated the influence of the modified diet on hepatic mitochondrial activity of two drugs, menadione and nimesulide, and FCCP, a classic protonophore, was used for comparison. The results showed that the effects of menadione and nimesulide were less severe on liver mitochondria for rats fed the modified diet than on rats fed the control diet. A specific effect on complex I seemed to be involved in drug-induced mitochondria dysfunction. Liver mitochondria from the modified diet group were more susceptible to nimesulide effects on MPT induction. The present work demonstrates that diet manipulation aimed at modifying mitochondrial membrane properties alters the toxicity of mitochondria active agents. This work highlights that diet may potentiate mitochondrial pharmacologic effects or increase drug-induced liabilities.